PERFORMANCE MEASUREMENT AND RISK MITIGATION OF PINEAPPLE SUPPLY CHAIN IN CENTRAL KALIMANTAN PROVINCE - Odi Andanu; Erni Dwi Puji Setyowati; Rakha Satya Idsan (Jurnal Teknologi Industri Pertanian, 2025)
Pineapple farmers and agro-processing businesses in Kapuas and Pulang Pisau face several risk. One significant risk is the lack of clarity regarding existing supply chain structures and performance, resulting in operational inefficiencies. This study aimed to identify and measure the performance of the pineapple agroindustry supply chain, analyze potential risks within the supply chain, and evaluate risk mitigation actions in the pineapple agroindustry located in Kapuas Regency and Pulang Pisau Regency, Central Kalimantan. The method used to analyze supply chain performance was the SCOR-AHP (Supply Chain Operations Reference-Analytic Hierarchy Process) method, while risk analysis was conducted using the HOR (House of Risk) method. The results showed that the highest supply chain performance score was attributed to the distributor, with a total score of 72.89, categorized as "good." Conversely, the lowest performance was seen among farmers, with a score of 42.55, classified as "marginal." The highest risk for farmers was the low selling price of pineapples, for collectors was price fluctuations, and for pineapple SMEs was inaccurate production planning and scheduling. The prioritized risk mitigation actions for farmers included optimizing the implementation of proper SOPs (Standard Operating Procedure) for pineapple cultivation and post-harvest processes, for collectors was the establishment of standards and agreements with farmers regarding pineapple quality, while the industry focuses on planning, optimizing, monitoring, and periodically evaluating the production process. Additionally, distributors should enhance the marketing reach of the products. Keywords: HOR, performance of supply chain, pineapple, risks, SCOR-AHP